The Role of Customer Insight in Improving the Perceived Mental of The Organization- An Exploratory Study of The Opinions of A Sample of Managers of Zain Iraq Mobile Communications Company: بحث استطلاعي لآراء عينة من مديري شركة زين العراق للاتصالات المتنقلة - Hammoodi AL-Attar, Fouad; Farhan Talib, Alaa; F. Abdali, Mahamood (Iraqi Journal for Administrative Sciences, 2023)
The aims of the research is to present the role of customer insight in improving the perceived mental image according to the opinions of a sample of managers of (Zain Iraq Mobile Communications Company). In order to achieve this, the customer insight variable was measured with its dimensions (customer attitudes, customer behavior, and customer culture) An explanatory variable. While the variable of mental image was measured with its dimensions (cognitive, emotional, and behavioralas a dependent variable. As for the research problem, it was represented by a main question, Can the researched company adopt the customer's insight to improve the perceived mental image?,. In order to achieve the objectives of the research and answer its questions, the descriptive analytical approach was adopted in presenting, analyzing, and interpreting information, while the questionnaire was used as a basic tool in collecting data and information, as (216) questionnaires were distributed to the managers of the researched company as an intentional sample. In addition, the research sought to test a number of main and sub-hypotheses related to the correlation and influence relationships between its variables, to find out the extent to which these variables were adopted, as well as to answer questions related to the research problem, in order to reach the desired. For the purpose of the analysis, I adopted a set of statistical tools in analyzing the data mean, and the statistical programs. The research reached a number of conclusions, the most important of which are: adopting the customer's insight into its dimensions as an explanatory variable that improves and enhances the perceived mental image of the researched company as a dependent variable. At the same time, presented a set of recommendations, most notably: the need for the company's management to pay more attention to the customer's insight variable and work to enhance it by adopting and applying its dimensions in the field, in a way that contributes to improving its perceived mental image.